Secagem de polpa de manga (Mangifera indica, L.) cv. Palmer em spray-dryer: condições de secagem e estabilidade - Rocha, Francisca de Oliveira (2017)
The mango is a typically tropical fruit that has fallen in the taste of the Brazilian consumer. The Palmer variety is well accepted in the intern market because it has large, aromatic fruits and no fiber. The objective of this research was to obtain powder of mango pulp cv. Palmer through spray-dryer dehydration, as well as perform the study of drying conditions, quality parameters and product stability. For this, the pulp characterization was carried out, followed by the analysis of the influence of the maltodextrin concentration (%) and drying air temperature (°C) on the humidity (%), hygroscopicity, yield (%) and color (L *, a *, b *), through an experimental planning (DCCE). Physical, physical-chemical and morphological characterization were performed in the powder. The adsorption isotherms were determined at temperatures of 25, 35 and 45ºC. The stability of the powder was also evaluated for a period of 90 days under four storage conditions: laminated packaging with and without vacuum, and polyethylene with and without vacuum. The results revealed that the physico-chemical parameters of fresh pulp are in accordance with the legislation for fruit pulp except for acidity, the best drying conditions for mango pulp cv. Palmer and with addition of 30% dehydrated maltodextrin at a temperature of 150 °C. In the mango powder with 30% maltodextrin dehydrated at 150 ° C, there was an increase of ºBrix, of the total and reducing sugars, as well as a reduction in the content of ascorbic acid, carotenoids, moisture and water activity. The increased concentration of the adjuvant maltodextrin provided powders with lower wall friction angle, greater ease of flow, higher apparent densities, larger particles and more dispersed with each other. The GAB model was the one that better adjusted the experimental data of the isotherms of the mango powders with 10, 20 and 30% of maltodextrin at temperatures of 25, 35 and 45ºC. The stability study showed that vacuum-laminated packaging was more efficient against moisture gain, offering a greater barrier to water vapor and greater color retention. It was concluded that maltodextrin concentration influenced the physical, physical-chemical and morphological characteristics of mango powder, the spray-dryer dehydration process resulted in the loss of nutrients such as ascorbic acid and carotenoids, mango powder remained well during the 90 days of stability, with the laminated vacuum packaging being the most recommended for storage.